2010
DOI: 10.1254/jphs.10158sc
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Analgesic Effect of the Rho Kinase Inhibitor AS1892802 in Rat Models of Chronic Pain

Abstract: Abstract. To assess the pharmacological profile of AS1892802, a novel and selective Rho kinase (ROCK) inhibitor, we examined the effects of repeated dosing with AS1892802 on models of monoiodoacetate-induced arthritis and streptozotocin-induced neuropathy. Although single dosing of AS1892802 exerted a short-acting, moderate analgesic effect, repeated dosing exhibited a longlasting and more potent analgesic effect in both models. Furthermore, the analgesic effect was sustained for seven days after the last admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…We have recently reported that a single dose of AS1892802 reduces both inflammatory and non-inflammatory pain (15) in rat models. The analgesic efficacy depended on blood concentration of the compound and maximum efficacy was obtained at the dose of 1 mg/kg (orally) 1 h after administration, but the activity disappeared within 24 h. In addition, analgesic activity was maintained by the repeated administration of the compound (41). The present results ( Fig.…”
Section: Discussionsupporting
confidence: 62%
“…We have recently reported that a single dose of AS1892802 reduces both inflammatory and non-inflammatory pain (15) in rat models. The analgesic efficacy depended on blood concentration of the compound and maximum efficacy was obtained at the dose of 1 mg/kg (orally) 1 h after administration, but the activity disappeared within 24 h. In addition, analgesic activity was maintained by the repeated administration of the compound (41). The present results ( Fig.…”
Section: Discussionsupporting
confidence: 62%
“…It has been reported that RhoA/ROCK induces over-activation of the cytoskeleton, which may act as a scaffold for the trafficking of nociceptive signaling factors. Moreover, the inhibition of RhoA/ROCK leads to the alleviation of neuropathic pain in mice 3134 . Our results show that rats pretreated with a ROCK inhibitor exhibited less hyperalgesia after SNL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another ROCK inhibitor (AS1892802) tested in a rat model of arthritis was similarly antinociceptive after oral (10 mg/kg) or intra-articular injection (3 μg) in inflamed knees ( 19 , 53 ). Yoshimi et al ( 20 ) observed no effect of this ROCK inhibitor, ie, neither nociception nor antinociception, after intra-articular injection in the noninflamed knee. One possible resolution to this paradox is to suggest that other kinases were inhibited by the doses of ROCK inhibitors that we were using (see below), that these other kinases were mediating these opposing effects and overcoming the pronociceptive effects of ROCK inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the participation of ROCKs in platelet aggregation, formation of stress fibres, focal adhesion, cellular motility ( 6 9 ) and monocyte transendothelial migration ( 10 ) has been described, which, collectively, suggest the involvement of ROCKs in inflammatory processes ( 11 13 ). Closer to the present context, ROCK activity has also been implicated in pain sensitivity responses such as those stimulated by cold ( 14 ), heat ( 15 , 16 ), formalin ( 17 ) and other stimuli ( 18 20 ). In addition, ROCKs have been implicated in the inhibition of acetylcholine release in peripheral cholinergic nerves ( 21 ).…”
mentioning
confidence: 90%